Osteitis in Chronic Rhinosinusitis: A State-of-the-Art Review - Wiyono Hadi; Widia Isa Aprillia Sujana (Siriraj Medical Journal, 2025)
Chronic rhinosinusitis (CRS) is characterized by inflammation of the nasal mucosa and paranasal sinuses. Mucosal inflammation can induce bone remodeling leading to osteitis. Paranasal sinus osteitis is a relatively new clinical finding, describing changes in the bone due to inflammation that will damage the lamellar bone structure and new bone formation. As many as 36-53% of CRS patients have osteitis, which makes CRS difficult to cure despite adequate management and is related to a substantial number of revision surgeries. Understanding all the evidence regarding osteitis in CRS is critical in discovering effective treatments for this incurable disease. Hence, we summarize the essential yet well-established features of osteitis in CRS, including the updated definition, the role of biofilm formation along with cytokines and runt-related transcription factor 2 axis as its possible underlying pathogenesis, the transforming growth factor beta signaling pathway of the disease, histopathological bone changes, radiographic staging and scoring systems, disease impacts on the CRS severity and quality of life, as well as the most up-to-date treatment strategies for osteitis in CRS. These include functional or radical endoscopic sinus surgery, interleukin-13 inhibitors, anti-biofilm agents, high-dose intranasal corticosteroids, and other potential therapies.